Perceived Contributions of a College Athletic Advising Program to Graduates - Yap, Susan E.; Nelson, Eileen S. (My University, 1999)
Research has indicated that college student-athletes face many challenges which may make resolving the developmental tasks in the age-relevant stage difficult. The present study examined contributions that the Office of Academic Development for Student-Athletes (OADSA) has made in terms of the accomplishment of certain tasks related to this critical transitional stage between adolescence and adulthood. First-year and transfer varsity athletes who were involved in the academic advising program in 1987 were interviewed over the telephone. There were a total of 46 (56%) former JMU athletes surveyed (30 men and 16 women). Results indicate that the former athletes reported themselves as satisfied with the OADSA and with the following developmental tasks: self-acceptance, making a contribution in a career, relating to others, achieving intimacy, and developing one's spirituality.
Keywords: student development; academic support; freshmen